Immunomodulatory role of Xenopus tropicalis immature Sertoli cells in tadpole muscle regeneration via macrophage response modulation - Qing Zhao; Irem Mertová; Aneta Wróblová; Světlana Žabková; Tereza Tlapáková; Vladimir Krylov (Stem Cell Research & Therapy)
Abstract Background Regenerative medicine and transplantation science continuously seek methods to circumvent immune-mediated rejection and promote tissue regeneration. Sertoli cells, with their inherent immunoprotective properties, emerge as pivotal players in this quest. However, whether Sertoli cells can play immunomodulatory role in tadpole tail regeneration and can thus benefit the regeneration process are needed to be discovered. Methods Immature Sertoli cells from Xenopus tropicalis (XtiSCs) were transplanted into X. tropicalis tadpoles, followed by the amputation of the final third of their tails. We assessed the migration of XtiSCs, tail regeneration length, muscle degradation and growth, and macrophage counts across various regions including the entire tail, tail trunk, injection site, and regeneration site. The interactions between XtiSCs and macrophages were examined using a confocal microscope. To deplete macrophages, clodronate liposomes were administered prior to the transplantation of XtiSCs, while the administration of control liposomes acted as a negative control. Student’s t-test was used to compare the effects of XtiSCs injection to those of a 2/3PBS injection across groups with no liposomes, control liposomes, and clodronate liposomes. Results XtiSCs have excellent viability after transplantation to tadpole tail and remarkable homing capabilities to the regeneration site after tail amputation. XtiSCs injection increased macrophage numbers at 3 days post-amputation and 5 days post-amputation in the tail trunk, specifically at the injection site and at the regenerated tail, in a macrophage depleted environment (clodronate-liposome injection). What’s more, XtiSCs injection decreased muscle fibers degradation significantly at 1 day post-amputation and facilitated new muscle growth significantly at 3 days post-amputation. In addition, whole-mount immunostaining showed that some XtiSCs co-localized with macrophages. And we observed potential mitochondria transport from XtiSCs to macrophages using MitoTracker staining in tadpole tail. Conclusions Our study delineates the novel role of XtiSCs in facilitating muscle regeneration post tadpole tail amputation, underscoring a unique interaction with macrophages that is crucial for regenerative success. This study not only highlights the therapeutic potential of Sertoli cells in regenerative medicine but also opens avenues for clinical translation, offering insights into immunoregulatory strategies that could enhance tissue regeneration and transplant acceptance.